A crucial nexus: Phylogenetic versus ecological support of the life-cycle of Ixodes ricinus (Ixodoidea: Ixodidae) and Borrelia spp. amplification - Agustin Estrada-Peña; Hein Sprong; Sara R. Wijburg (Current Research in Parasitology and Vector-Borne Diseases)
The tick Ixodes ricinus parasitizes a wide range of vertebrates. These hosts vary in the relative contribution to the feeding of the different tick life stages, and their interplay is pivotal in the transmission dynamics of tick-borne pathogens. We aimed to know if there is a phylogenetic signal in the feeding and propagation hosts of I. ricinus, independently of other traits, as well as in the amplification of Borrelia burgdorferi (s.l.) in feeding larvae. We used a compilation of 1127 published field surveys in Europe, providing data for 96,586 hosts, resulting in 265,124 larvae, 72,080 nymphs and 37,726 adults. The load of immature ticks on hosts showed a significant phylogenetic signal towards the genera Psammodromus, Podarcis, and Lacerta (nymphs only). We hypothesize that such signal is the background hallmark of the primitive hosts associations of I. ricinus, probably in the glaciation refugia. A secondary phylogenetic signal for tick immatures appeared for some genera of Rodentia and Eulipotyphla. Results suggest the notion that the tick gained these hosts after spread from glaciation refugia. Analyses support a phylogenetic signal in the tick adults, firmly linked to Cetartiodactyla, but not to Carnivora or Aves. This study provides the first demonstration of host preferences in the generalist tick I. ricinus. We further demonstrate that combinations of vertebrates contribute in different proportions supporting the tick life-cycle in biogeographical regions of the Western Palaearctic as each region has unique combinations of dominant hosts. Analysis of the amplification of B. burgdorferi (s.l.) demonstrated that each genospecies is better amplified by competent reservoirs with which a strong phylogenetic signal exists. These vertebrates are the same along the spatial range: environmental traits do not change the reservoirs along the large territory studied. The transmission of B. burgdorferi (s.l.) is amplified by a few species of vertebrates, that share biogeographical regions with the tick vector in variable proportions.